Supercooling suppression in the tetrahydrofuran clathrate hydrate formation. Issue 38 (14th September 2022) - Machida, Hironobu; Sugahara, Takeshi; Hirasawa, Izumi
Abstract : The addition of silver(ii ) oxide effectively diminishes the degree of supercooling in the tetrahydrofuran hydrate formation. Abstract : Generally, supercooling as large as about 25 K is necessary to form tetrahydrofuran clathrate hydrate (THF hydrate). In the present study, we have investigated how the existence of various additives affects the degree of supercooling (Δ T ) in the THF hydrate formation without any external stimulus. The addition of either AgO or Ag3 PO4 yields the best Δ T suppression, where Δ T was approximately 4 K, much smaller than 25 K. Raman spectra reveal that, in the supercooled THF aqueous solution with AgO before crystallization, the THF molecule forms a coordination bond with AgO, whereas it forms a hydrogen bond with a water molecule in the system without AgO. The oxygen atom of the THF molecules, which is a hydrogen-bonding site, was oriented to a AgO molecule in the aqueous solution. The orientation and the subsequent interruption of the hydrogen bond make it easy to form a hydration shell around the THF molecule. Scanning Transmission Electron Microscopy images by using the freeze-fracture replica method reveal that a cluster, which is the smallest structural unit of a crystal, includes Ag-containing nanoparticles formed from AgO or Ag3 PO4, which accelerate the cluster formation. As a result, the addition of AgO or Ag3 PO4 effectively diminishes the degree of supercooling in the THF hydrate formation.